IDENTIFICATION AND IMPROVING THE NUTRITIONAL VALUE OF A TYPE OF BREAD - Carrión Muñoz, Rolando (1999)
This paper presents the approach of the investigation being conducted by the author on the subject, with particular emphasis on aspects of nutrition and replacing the traditional inputs.